2021
DOI: 10.3390/ijerph18147509
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Physical Restraints on Geriatric Patients: Culture and Attitudes among Healthcare Professionals at Intermediate Care Hospitals in Majorca. A Qualitative Study Protocol

Abstract: The use of physical restraints is a common practice in the care of hospitalised and institutionalised elderly people. This use is determined by factors related to the patients, their families, the healthcare professionals, the institution, and prevailing social values. Today, however, this practice is often questioned because of its physical, psychological, moral, ethical, and legal repercussions. The present study explores attitudes among healthcare professionals towards the physical restraint of geriatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…The different views of the diverse stakeholders show the need for a joint approach to in‐depth knowledge of the needs and problems generated by restraints, as well as possible improvements in its use, organizational factors and regulation. The discourse is expected to vary according to the respondent's area of professional activity (Carrero‐Planells et al., 2021 ), yet, previous research has been conducted mainly among nurses, but none has been conducted with all the professional stakeholders involved in nursing home care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The different views of the diverse stakeholders show the need for a joint approach to in‐depth knowledge of the needs and problems generated by restraints, as well as possible improvements in its use, organizational factors and regulation. The discourse is expected to vary according to the respondent's area of professional activity (Carrero‐Planells et al., 2021 ), yet, previous research has been conducted mainly among nurses, but none has been conducted with all the professional stakeholders involved in nursing home care.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there was no consensus regarding the restraint‐free model. This is particularly important because it has been stated that healthcare professionals who generally approve of the use of physical restraints may normalize the situation and make more extensive use of these measures, whilst professionals who reject physical restraints may perform actions of resistance to minimize their use (Carrero‐Planells et al., 2021 ). The concept of safety, in terms of the patient's physical safety, was frequently mentioned, with consensus on the justification of the measure in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published review focused on the efectiveness of IC found that bedbased IC is linked with reduced readmission rates and length of hospital stay [14]. Furthermore, recent studies exploring experiences and perceptions of healthcare professionals from an IC setting focused on understanding patient's participation in IC [4,15] and the attitudes of healthcare professionals towards the physical restraints on patients in IC [16].…”
Section: Introductionmentioning
confidence: 99%